Simulasi numerik kombinasi perpindahan panas konveksi alami dan radiasi pada square cavity - Syamsuri Syamsuri; Suheni Suheni; HS Maulana; Muhammad Syafii (TURBO [Tulisan Riset Berbasis Online], 2019)
Natural convection is very important in some cases such as glass windows, solar collectors, electronic measuring devices (cooling devices for electronic instruments) and building materials that use insulation. In this research, will be seen the phenomenon of natural convection that occurs in square cavity. The method used for simulation is computational fluid dynamics or CFD. The model used is the 2D cavity model. In this simulation the value of Rayleigh Number (Ra) was varied i.e. 103,104,105 and 106. From this research, it is found that the higher the value of Ra in cavity, the higher the value of the average Nusselt Number (????̅???? ) on the wall which has a high temperature. Ra = 103 so that ????̅???? = 1.17. Ra =104, so that ????̅???? = 2.2. Ra = 105, so that ????̅???? = 4.47. Ra = 106, and then so that ????̅???? = 8.95. Based on the value and contour of the flow the smaller the Ra value in the square cavity, the isothermal line phenomenon that appears will be more vertical. The greater the Ra value in the cavity, the contour of the stream function will change to an ellipse and finally two vortices will appear.Keywords: Numerical simulation, konveksi, radiasi, square cavity.